Students’ E-complaints on the Promises and Pitfalls of Blended Learning: A Socio-Pragmatic Analysis - Justin Banguis; Presley Fortes Divino; Christian Jay O. Syting; Karl Christian Maintang (CV. Tripe Konsultan, 2023)
This study aimed to identify the linguistic make up of the 100 students’ e-complaints related to blended learning in the Philippines. The impoliteness strategies and how they are being used in each complaint were unraveled through a socio-pragmatic analysis. Furthermore, the study also examined what politeness strategies were violated in their complaints. In terms of impoliteness strategies, it involves the following: bald on record impoliteness, asserting, claiming, commanding, complaining, deploring, describing, explaining, planning, questioning, and suggesting; mock politeness, commanding, describing, questioning, requesting, stating, and suggesting; negative politeness, asserting, deploring, suggesting; positive politeness, stating, and swearing. On the other hand, the politeness strategies violated include bald on record politeness, positive politeness, negative politeness, and off record politeness. This study demonstrates the significance of recognizing impoliteness and its effects, particularly when posting complaints online. As a result, a complaint that appears to be polite is not always polite. In regard to other elements, such as social emotions and civility, direct and/or implicit attacks employed in complaints might still be considered disrespectful if they are unaware of the strategies that embody politeness and impoliteness.